KAJIAN SEMIOTIKA BARTHES PADA KARTUN MICE TAHUN 2022 - I Wayan Nuriarta (Universitas Bunda Mulia, 2023)
This study uses a qualitative design to collect, filter and analyze data. The subject of this research study was Mice cartoons in Kompas Newspaper in 2022. The selection of cartoons used a purposive sampling technique. Purposive sampling is sampling adjusted to the research objectives. From a number of observed cartoons, cartoons published on January 23, 2022 and March 6, 2022 were chosen as samples because these cartoons show how to express comics with issues of novelty regarding IKN (National Capital City) and the extension of the presidential term. These two issues were issues at the beginning of the year that warmed up because they were connected by political discourse ahead of the 2024 Election. IKN and the three-term president have a connection in politics. The object of this study is focused on comic analysis using McCloud's comic theory, denotative meaning and connotative meaning using Barthes' semiotic theory. The results of the study show that the denotation meaning of the Mice cartoon is a picture of the Indonesian people who are in dialogue, either dialogue between colleagues or dialogue between the people and their officials. This dialogue is presented in black and white comic panel transitions. This panel transition creates a narrative or story for the reader. The narrative can also be interpreted connotatively. The connotative meaning of Mice's cartoons shows that there is something that is discussed further in relation to the context of the discourse raised when compared to the witty visualization. There is a serious problem covered in a humorous cartoon appearance. The name of the IKN is still being debated by several groups, the issue of names is being seriously discussed, and the three-term presidential discourse is considered to be possible if the president wants it.